EFEKTIVITAS PEMBERIAN SOYBEAN (Glycine Max) DALAM PENINGKATAN ASI IBU MENYUSUI DIWILAYAH KERJA PUSKESMAS KOTA PEKANBARU - Ade Febriani; Nova Yulita; Sellia Juwita (LPPM Universitas Abdurrab, 2020)
Mother's Milk (ASI) is the best food that contains all nutrients needed by infants aged 0-6 months. Breast milk also contains immune substances that will protect babies from various infectious diseases, bacteria, viruses, parasites, and fungi. Breast milk can affect the growth and development of infants, including mental emotional development through attachment formed through breastfeeding. Soybeans are one of a variety of good sources of protein for the body. One of the ingredients is phytoestrogens which when consumed routinely by breastfeeding mothers will help mothers to increase abundant and abundant milk production and get good quality milk. The purpose of this study was to determine the effect of soybean consumption on breast milk production in breastfeeding mothers in the Rumbai working area of ​​Pekanbaru. The research method is an experiment (quasi experiment). The design of this study used the One Group Pretest-Postest design. Where there is no comparison group (control), but there has been a first observation (pre-test) that the researcher might be able to test changes that occur after the experiment. This research was conducted in the working area of ​​the Rumbai Health Center conducted in April 2019 to July 2019. The results of the research are that the respondent of ASI production is smooth, that is 14 people, 46.7%), ASI is slightly smooth, 11 people (36.3%), and ASI is very smooth, 6 people (20%). Increased ASI production after being given soybean by 24 people (80%) with the category of ASI very smooth and 6 people ASI smooth (20%). The results of this test indicate the value of p = 0,000 (p <0.05). Based on the results of the study, it can be concluded that there is an effect of soybean consumption on breastfeeding mothers on breast milk production and an increase in milk production in breastfeeding mothers.